Physicochemical variability of agricultural soils in the bulb onion (Allium Cepa L.) crop of the irrigation and drainage district Usochicamocha in Boyacá, Colombia (2022)
The bulb onion crop, besides being one of the main vegetable crops worldwide for Boyacá, is considered one of the pillars of the regional agricultural economy. Despite being so important from the economic aspect, at the agricultural level this crop has several problems among which stand out the nutritional requirements of the crop and poor practices in terms of soil management and conservation. That is why it is important to understand the physicochemical variability of the soil associated with the crop and how these can be related to intrinsic processes at a local geographic scale. To determine the variability of soil physicochemical conditions in the bulb onion crop, a total of 15 zones of 50m x 50m within the Usochicamocha irrigation district were analyzed. Soil samples were collected and subsequently analyzed in the laboratory. Information was obtained on parameters such as pH, OM%, ED, bulk density, soil texture, Ca, Mg, K, Na and P. The soil data obtained allowed us to observe the grouping patterns of study zones which have no geographical incidence, suggesting that intrinsic characteristics of the crops such as agricultural practices would play a more important role in the physicochemical variability than extrinsic factors such as the ecogeographic range of the zone. Our results support efforts to continue exploring the variability of soil physicochemical conditions within a crop and how these may relate to local soil management and conservation practices after each harvest season.